1984
DOI: 10.1007/bf01978916
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological control of leukotriene and prostaglandin production from mouse peritoneal macrophages

Abstract: Leukotriene and prostaglandin production by mouse peritoneal macrophages was investigated. It could be shown that the tumour promoter 12-O-tetradecanoylphorbol-13-acetate initiated the release of prostaglandin E2 but had little effect on the release of leukotriene C4-like immunoreactivity. The divalent cation ionophore A 23187 at concentrations between 10(-6) and 10(-8) mol/l initiated prostaglandin as well as leukotriene release. This prostaglandin and leukotriene release could be modulated by drugs. Non-ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…2 4 Second, cyclooxygenase blockade could result in diversion of arachidonic acid into the lipoxygenase pathway, thereby causing increased leukotriene production with consequent collateral vessel constriction. 5 Finally, a direct vasoconstrictor action, which appears to be independent of cyclooxygenase inhibition, has been reported for indomethacin and might account for the observed findings.6…”
mentioning
confidence: 70%
“…2 4 Second, cyclooxygenase blockade could result in diversion of arachidonic acid into the lipoxygenase pathway, thereby causing increased leukotriene production with consequent collateral vessel constriction. 5 Finally, a direct vasoconstrictor action, which appears to be independent of cyclooxygenase inhibition, has been reported for indomethacin and might account for the observed findings.6…”
mentioning
confidence: 70%
“…Sigma), an inhibitor of the lipoxygenase pathway [Brune et al, 1984], for 15 min and chal lenged with indomethacin (3 x 10'1 ' M). Stock solu tions of indomethacin and NDGA were dissolved in ethanol before use.…”
Section: Methodsmentioning
confidence: 99%
“…This product also formed when PMA was replaced by 1,2-dioctanoyl-sn-glycerol. Leukotriene C is known to be formed in macrophages responding to zymosan or calcium ionophore [4][5][6] and its formation is throught to require an increase in cytosolic calcium [15]. The total mobilization of arachidonic acid in response to the combination of PMA and 1,2-Ip 3-0-C10 was also greater than that seen with each of the agents separately.…”
Section: Resultsmentioning
confidence: 82%
“…Figure 3 also depicts a time-dependent increase in the labeling of phosphatidylinositol 4-phosphate and phosphatidylinositol 4,5-bisphosphate, which was shown in separate experiments to correspond to relative increases in each phosphoinositide of 50-100 percent (at 20 pM 1,2-Ip 3-0-Ct0). Previous studies in peritoneal macrophages have shown that activators of protein kinase C, such as PMA or 1,2-dioctanoyl-sn-glycerol provoke release of arachidonic acid from the major phospholipids and degradation of phosphatidylinositol by a phospholipase A pathway [1,2], selective formation of prostaglandin E z [4,5,13] and a characteristic pattern of protein phosphorylation [3]. Analysis of individual phospholipids showed that, at variance with the PMA-induced mobilization of arachidonic acid from ethanolamine, choline and inositol phosphoglycerides, the glycerol ether caused virtually no liberation from choline phosphoglycerides (Table I).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation